Safety and immunogenicity of influenza A(H5N1) vaccine stored up to twelve years in the National Pre-Pandemic Influenza Vaccine Stockpile (NPIVS). Issue 3 (14th January 2019) - Oshansky, Christine M.; Zhou, James; Gao, Yonghong; Schweinle, Jo Ellen; Biscardi, Karen; DeBeauchamp, Jennifer; Pavetto, Corrina; Wollish, Amy; Webby, Richard J.; Cioce, Vittoria; Donis, Ruben O.; Bright, Rick A.; et al.
Abstract: Background: As part of the U.S. Department of Health and Human Services (HHS) Pandemic Influenza Plan preparedness and response strategy, the National Pre-Pandemic Influenza Vaccine Stockpile (NPIVS) program was established by the Biomedical Advanced Research and Development Authority (BARDA) in 2005 with the goal of building and maintaining a stockpile of vaccines for influenza viruses with pandemic potential to vaccinate 20 million people in the critical workforce in the event of a pandemic. The NPIVS program continuously monitors the integrity of influenza vaccine antigens and adjuvants stored within the stockpile. In addition to monitoring physical and chemical properties in stability studies, it is important to regularly assess the safety and immunogenicity of stockpiled vaccines and adjuvants to maintain preparedness for use in the event of an influenza pandemic. Methods: BARDA conducted a randomized, double-blinded Phase 2 clinical study with the oldest stockpiled influenza A(H5N1) antigen, stored over the previous 10–12 years administered with or without MF59® adjuvant, stored over the previous 2–7 years at the time of vaccination. Results: Stockpiled vaccines were well-tolerated, adverse events were generally mild, and there was no drop in immunogenicity to the oldest stockpiled A(H5N1) vaccine. Compared to unadjuvanted vaccine, greater peak antibody responses were observed in subjects who were vaccinated with MF59-adjuvanted vaccines, regardless of antigen dose. Vaccination with the A(H5N1) vaccine antigen also results in cross-reactive antibody responses to contemporary circulating strains of A(H5) influenza viruses. Conclusions: The frequency, type, and severity of AEs observed during this study are similar to historical clinical study data with A(H5N1) vaccines and MF59 adjuvant indicating that a stockpiled A(H5N1) vaccine appears to remain safe and tolerable. The vaccines were immunogenic when administered as a two-dose vaccine regimen in healthy adults, despite extended storage of HA antigen or MF59 adjuvant within the NPIVS. Trial registration: ClinicalTrials.gov : NCT02680002.